THE IMPACT OF COST LEADERSHIP ON FINANCIAL DISTRESS MEDIATED ENVIRONMENTAL, SOCIAL, AND GOVERNANCE - Asher, Steven; Meythi, Meythi; Martusa, Riki; Rapina, Rapina (UI Scholars Hub, 2025)
Background: This study investigates the mediating role of environmental, social, and governance (ESG) performance in the relationship between cost leadership and financial distress among companies in Indonesia. Methods: Using path analysis, the research analyzed a sample of 43 firms listed on the Indonesia Stock Exchange from 2018 to 2022. Findings: The findings indicate that cost leadership positively affected ESG; however, no direct relationship was observed between cost leadership or ESG and financial distress. The mediation analysis reveals that ESG acted as a mediator, linking cost leadership to a reduced risk of financial distress. Conclusion: These results highlight the importance of integrating cost leadership with ESG practices to strengthen corporate financial resilience. Novelty/Originality of this article: The study has offered valuable insights for companies and stakeholders looking to improve sustainability practices that could mitigate the risk of financial distress.